2015
DOI: 10.1073/pnas.1509250112
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic levitation of single cells

Abstract: Several cellular events cause permanent or transient changes in inherent magnetic and density properties of cells. Characterizing these changes in cell populations is crucial to understand cellular heterogeneity in cancer, immune response, infectious diseases, drug resistance, and evolution. Although magnetic levitation has previously been used for macroscale objects, its use in life sciences has been hindered by the inability to levitate microscale objects and by the toxicity of metal salts previously applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
304
1
20

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 205 publications
(332 citation statements)
references
References 48 publications
7
304
1
20
Order By: Relevance
“…4). One of the studies showed that metastatic lung, breast and pancreatic cancer cells were 70% softer than benign cells31 and cancer cells over all have lower densities65. Nucleus stiffness also follows a similar trend; loss of Lamin A/C during carcinogenesis leads to a decrease in the stiffness and an increase in the elasticity of the nucleus66.…”
Section: Discussionmentioning
confidence: 95%
“…4). One of the studies showed that metastatic lung, breast and pancreatic cancer cells were 70% softer than benign cells31 and cancer cells over all have lower densities65. Nucleus stiffness also follows a similar trend; loss of Lamin A/C during carcinogenesis leads to a decrease in the stiffness and an increase in the elasticity of the nucleus66.…”
Section: Discussionmentioning
confidence: 95%
“…iii) MagLev can be used to perform a range of important, density-based bioanalyses. [13][14][15][16][17] iv) The simplicityof-use, portability, and low cost of MagLev make it particularly attractive for use in resource-limited settings (e.g., schools, mines, archeological sites, field operations, and laboratories in the developing countries).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, using magnetically functionalized electrospun matrices with magnetic nanoparticles [23] as well as using tissue spheroids biofabricated from cells labelled with magnetic nanoparticles [24][25][26][27] will enable the development of novel magnetic 3D bioprinting technology based on principles of magnetic levitation or translocation of tissue constructs using magnetic forces [28][29][30] .…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that tissue spheroids can attach, spread and fuse on synthetic electrospun matrices [21,22] . Moreover, recently reported magnetic functionalization of electrospun synthetic matrices with magnetic nanoparticles [23] as well as biofabrication of tissue spheroids from cells labelled with magnetic nanoparticles [24][25][26][27] allow the development of magnetic forcesdriven biofabrication and even 3D magnetic bioprinting based on principles of magnetic levitation [28][29][30] . Thus, application of nanotechnology can enable development of novel technology of magnetic 3D bioprinting.…”
Section: Introductionmentioning
confidence: 99%